Pengembangan Nilai-Nilai Pendidikan Pancasila dalam Menumbuhkan Sikap Antikorupsi Mahasiswa Institut Teknologi Pln - Yuliansyah Yuliansyah; Jumiati Jumiati; Sri Yayi (Jurnal Syntax Admiration, 2023)
This study aims to determine the effectiveness of adding anti-corruption material to Pancasila education courses in universities in fostering anti-corruption attitudes for PLN Institute of Technology students. This research uses a correlational survey-descriptive method, namely research conducted to obtain information about data, with the preliminary study stages carried out with a quantitative descriptive approach. The development stage is carried out with limited trials on conventional teaching of lecturers by applying experimental methods (single oneshot case study). The results showed that the development of Pancasila educational values can contribute significantly in fostering anti-corruption attitudes in students. Values such as honesty. Institut Teknologi Pln integrity, responsibility, fairness, and the spirit of mutual assistance are considered important in shaping anti-corruption attitudes. In addition, the role of educational institutions and the surrounding environment is also very influential in shaping anti-corruption attitudes in students. It can be concluded that the development of Pancasila educational values is very important in fostering anti-corruption attitudes in students. Values such as honesty, integrity, responsibility, fairness, and the spirit of mutual assistance can shape character and behavior that is honest, responsible, fair, and has the spirit of mutual assistance in maintaining honesty and fighting corruption.